Sistem Sortasi Biji Kopi Otomatis Menggunakan Sensor Warna TCS34725 dan Arduino Mega 2560 - Zandianto, Alex; Mahrijal, Mahrijal; Irwan, Irwan (Jurnal Inovasi Teknologi Terapan, 2026)
This research aims to design and develop an automatic coffee bean sorting system based on color and weight using the TCS34725 color sensor, HX711 load cell, stepper motor, servo motor, and an Arduino Mega 2560 microcontroller. The system is proposed to address the limitations of conventional manual sorting, which is time-consuming and inconsistent in quality. The methodology includes hardware design, electronic integration, microcontroller programming, and performance testing on coffee beans with various color categories. The TCS34725 sensor is used to capture RGB values for color classification, while the load cell measures the accumulated weight of sorted beans until reaching the predefined target. Experimental results show that the developed system achieves a color detection accuracy of 92.5% and a weight measurement error of 1.8 grams on average. Furthermore, the system is capable of stopping automatically when the target weight is reached. In conclusion, the proposed sorting system enhances efficiency and consistency in coffee bean classification and has potential applications for small industries and coffee-processing SMEs.